2011
DOI: 10.1074/jbc.m110.175638
|View full text |Cite
|
Sign up to set email alerts
|

The Oligomeric State and Arrangement of the Active Bacterial Translocon

Abstract: Protein secretion in bacteria is driven through the ubiquitous SecYEG complex by the ATPase SecA. The structure of SecYEG alone or as a complex with SecA in detergent reveal a monomeric heterotrimer enclosing a central protein channel, yet in membranes it is dimeric. We have addressed the functional significance of the oligomeric status of SecYEG in protein translocation using single molecule and ensemble methods. The results show that while monomers are sufficient for the SecA- and ATP-dependent association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
117
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(124 citation statements)
references
References 36 publications
7
117
0
Order By: Relevance
“…Two distinct dimeric arrangements have been observed in the lipid bilayer and in detergent solution: the front-to-front where the SecY lateral gates are facing each other and the back-to-back with the SecE subunits at the interface (20,21,(32)(33)(34). The nanodiscs allowed to probe the orientation of the SecY dimer in a restricted environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinct dimeric arrangements have been observed in the lipid bilayer and in detergent solution: the front-to-front where the SecY lateral gates are facing each other and the back-to-back with the SecE subunits at the interface (20,21,(32)(33)(34). The nanodiscs allowed to probe the orientation of the SecY dimer in a restricted environment.…”
Section: Resultsmentioning
confidence: 99%
“…In possible support to the model, a photo-cross-linking analysis in intact cells showed that SecA can simultaneously contact two SecYs (20). More recently, a single molecule analysis in proteoliposomes indicated that a single SecY was sufficient to bind the preprotein, although the dimer was necessary to support significant transport (21). These earlier studies have indicated the importance of the dimer, but the exact role of each copy requires additional support.…”
mentioning
confidence: 88%
“…However, despite major research, the true oligomeric state of SecA remains highly controversial (18). This is further complicated by the different models suggesting association of both the monomeric and dimeric forms of SecA to the SecYEG translocon (27)(28)(29)(30), although the structure of the SecA-SecYEG complex suggests a 1:1 interaction (10). The structure of the SecA-SecYEG complex was a major achievement, but it failed to explain the observed interactions between SecA and SecYEG during translocation (10,(31)(32)(33).…”
mentioning
confidence: 99%
“…It is clear that the channel for transfer of polypeptides lies within a monomer of SecY (1,(15)(16)(17)(18); however, SecYEG exists as monomers, dimers, and higher oligomers (19)(20)(21)(22)(23)(24). Therefore, much controversy has arisen surrounding the question of whether the active translocase comprises a SecYEG monomer or dimer (17,(25)(26)(27)(28). One idea is that an idle unit of SecYEG might be involved in stabilizing the translocase, perhaps through binding to SecA (17,25,26).…”
mentioning
confidence: 99%
“…Therefore, much controversy has arisen surrounding the question of whether the active translocase comprises a SecYEG monomer or dimer (17,(25)(26)(27)(28). One idea is that an idle unit of SecYEG might be involved in stabilizing the translocase, perhaps through binding to SecA (17,25,26).…”
mentioning
confidence: 99%